The investigation of a wake potential of non-relativistic protons in the case of their orientation motion in solid-state plasma of ionic crystals - Maksyuta, M.V.; Vysotskii, V.I.; Martysh, Ye.V. (Вопросы атомной науки и техники, 2017)
For non-relativistic protons channeled along the planes (axes) in ionic crystals the time-dependent induced electric dipole moments of the crystalline medium ions under the influence of protons electric fields are calculated. For this dipoles system the summary non-stationary scalar potential both in planar and axial cases is found. At this on the example of an axial orientation motion it is shown that this potential can be expanded on two components, one of which contributes to the interaction potential of the channeled protons with the crystal lattice, and the other, correspondingly, appears in the form of so-called “wake potential”, effecting only protons velocity. Для каналируемых вдоль плоскостей (осей) в ионных кристаллах нерелятивистских протонов рассчитываются зависящие от времени наведенные электрические дипольные моменты ионов кристаллической среды, формируемые под воздействием электрических полей протонов. Для этой системы диполей находится суммарный нестационарный скалярный потенциал как в плоскостном, так и в осевом случаях. При этом на примере ориентационного движения вдоль осей кристалла показывается, что такой потенциал можно разложить на два слагаемых, одно из которых вносит вклад в потенциал взаимодействия каналируемых протонов с кристаллической решёткой, а другое, соответственно, проявляется в виде так называемого “кильватерного потенциала”, влияющего только на скорость протонов. Для канальованих уздовж площин (осей) в іонних кристалах нерелятивістських протонів розраховуються залежні від часу наведені електричні дипольні моменти іонів кристалічного середовища, які формуються під впливом електричних полів протонів. Для цієї системи диполів знаходиться сумарний нестаціонарний скалярний потенціал як у площинному, так і в осьовому випадках. При цьому на прикладі орієнтаційного руху уздовж осей кристала показується, що такий потенціал можна розкласти на два доданка, один з яких вносить вклад у потенціал взаємодії канальованих протонів з кристалічною граткою, а інший, відповідно, проявляється у вигляді так званого “кільватерного ефекту”, впливаючого лише на швидкість протонів.